Overexpression of nuclear AR-V7 protein in primary prostate cancer is an independent negative prognostic marker in men with high-risk disease receiving adjuvant therapy - Chen, Xin; Heller, Martina; Nientiedt, Cathleen; Falkenstein, Michael; Herpel, Esther; Jenzer, Maximilian; Grüllich, Carsten; Jäger, Dirk; Hohenfellner, Markus; Duensing, Stefan; Sültmann, Holger; Debus, Jürgen (Urologic oncology, 2018)
Background Overexpression of the androgen receptor (AR) splice variant 7 (AR-V7) has recently been reported to be associated with resistance to antihormonal therapy. Herein, we address the question whether tumor cells with AR-V7 expression can be detected at the time of radical prostatectomy, that is, before long-term hormonal manipulation and castration resistance, and what the potential prognostic impact on the biochemical recurrence (BCR)-free survival may be.Methods An anti-AR-V7 antibody was first validated in a training set of prostate cancer specimens by a comparison of AR-V7 protein to AR-V7 mRNA expression. We then analyzed nuclear AR-V7 protein expression in the primary tumors and lymph node metastases from 163 predominantly high-risk patients (cohort I) as well as the primary tumors from patients of a second, consecutive patient cohort (n = 238, cohort II) not selected for any clinicopathological features. Staining results were correlated to patient characteristics and BCR-free patient survival.Results High nuclear AR-V7 protein expression was detected in approximately 30%-40% of patients in cohort I and II at the time of radical prostatectomy. High baseline expression of nuclear AR-V7 protein was associated with an unfavorable BCR-free survival in the high-risk patient cohort I but not in the unselected consecutive cohort II. Remarkably, AR-V7 was an independent negative prognostic factor in high-risk prostate cancer patients of cohort I who were selected to receive adjuvant treatment.Conclusions Prostate cancer cells with high nuclear AR-V7 protein expression can be detected in a substantial proportion of tumors at the time of radical prostatectomy. The presence of AR-V7-positive tumor cells is associated with an unfavorable prognosis for BCR-free survival in a high-risk patient cohort including a subgroup of patients selected to receive adjuvant therapy, in which AR-V7 was an independent negative prognosticator. Overexpression of nuclear AR-V7 protein hence identifies a subset of tumors with remarkably aggressive growth characteristics among clinically and histologically high-risk patients at the time of radical prostatectomy.
Gesehen am 02.07.2018
Available online 1 December 2017